If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (24x + 2) + 4 = 46 Reorder the terms: (2 + 24x) + 4 = 46 Remove parenthesis around (2 + 24x) 2 + 24x + 4 = 46 Reorder the terms: 2 + 4 + 24x = 46 Combine like terms: 2 + 4 = 6 6 + 24x = 46 Solving 6 + 24x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 24x = 46 + -6 Combine like terms: 6 + -6 = 0 0 + 24x = 46 + -6 24x = 46 + -6 Combine like terms: 46 + -6 = 40 24x = 40 Divide each side by '24'. x = 1.666666667 Simplifying x = 1.666666667
| 12(0)-2y=-14 | | (26x+3)+56=45 | | -24(0)-3y=1 | | -3-4y=-5 | | -2(-4.5)+2y=-10 | | 7(-4)-4y=-16 | | (12c^10)/(4c^14) | | 4(0)+2y=-4 | | x-4/5=-1/5 | | (10c^10)/(4c^14) | | .075=(.075)x^2+(29.43) | | C+(4-3c)=0 | | -8(0)-2y=-2 | | 5x-20+3x+30=7x+20 | | 12c^10/4c^14 | | 7x-4(-2x-11)=-16 | | 12c^10/4c14 | | 4x+2(-2x-1)=-4 | | 8x^2-36x+36=25 | | -x-(-5x+4)=4 | | -8x-2(-4x+1)=-2 | | -4x-7(6x+4)=18 | | -4x-(-4x+8)=-3 | | 7(t-3)=2(t-9)+2r | | 6a-11a=7 | | -2x+4(3x)=-10 | | 2x+4+5x+10+3x=84 | | 121x^2+169=0 | | -5x-4(2x+4)=23 | | 4x+2(2x-18)=20 | | -4x-(-4x-12)=12 | | 7x+6(-6x+3)=-11 |